Generation of thiyl radicals in a zinc(ii) porous coordination polymer by light-induced post-synthetic deprotection. Issue 38 (23rd April 2018) - Kusaka, Shinpei; Matsuda, Ryotaro; Kitagawa, Susumu
Abstract : Generation of a highly reactive sulfur species in nanospace is demonstrated via the photo-dissociation of disulfides. Abstract : Kinetic stabilisation of unstable chemical species in nanospace is of potential importance in the field of materials and synthetic chemistry, and porous coordination polymers (PCPs) represent a facile platform to provide such reaction fields. Thiyl radicals are important reactive substances that often play a leading role in organic and bioorganic chemistry. However, their generation in nanospace has been barely investigated due to synthetic difficulties. Here, we report a facile methodology for the functionalisation of active thiyl substituents on PCP pore surfaces using a post-synthetic protection and deprotection technique. The thiyl radicals were generated inside a zinc(ii )-based PCP upon the deprotection of asymmetric disulfides, which were used as the protecting groups by ultraviolet light irradiation.